Biblos Vol. 26, n. 2 (2012) (Pesquisa Brasileira em Ciência da Informação e Biblioteconomia, 2013)
Biblos Vol. 26, n. 2 (2012)Link de acesso ao númerohttp://www.seer.furg.br/biblos/issue/view/405/showToc